Intellegent Sytems for Disaster Management : Anmanned Aerial Vehicles - DÜNDAR, Uğurcan (My University, 2019)
This paper formulates the UAVs' surveillance problem as a location-routing problem, where limited energy capacities of UAVs are modeled explicitly as constraints that account for their different flight statuses. The formulation decides for the locations of capacitated stations to swap the batteries of UAVs, and their routes to visit a number of known target points. We also formulate novel subtours elimination constraints, which eliminate all subtours that do not start and end at the main depot. Our formulation can be applied for the risk mitigation phase of disaster management, where the risk of a disaster is reduced through constant monitoring of the disaster area (area at which refugee boats usually sink) by UAVs.
Keywords: Intelligent Systems; Location-Routing Problems; Mixed-Integer Linear Programming; Risk Mitigation Phase